2018
DOI: 10.3389/fpsyt.2018.00389
|View full text |Cite
|
Sign up to set email alerts
|

Emotion Transfer, Emotion Regulation, and Empathy-Related Processes in Physician-Patient Interactions and Their Association With Physician Well-Being: A Theoretical Model

Abstract: Physicians experience many emotionally challenging situations in their professional lives, influencing their emotional state through emotion contagion or social appraisal processes. Successful emotion regulation is crucial to sustain health, enable well-being, foster resilience, and prevent burnout or compassion fatigue. Despite the alarmingly high rate of stress-related disorders in physicians, affecting not only physician well-being, but also outcomes such as physician performance, quality of care, or patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 123 publications
0
35
0
5
Order By: Relevance
“…In addition to a theoretical point of view, the Vicarious Experience and Intuitive Understanding components are also relevant from a clinical perspective in cases of pathology in which the exact deficits in empathy and intersubjectivity remain a topic of discussion (e.g., [88,8994]) and constitute possible targets of intervention, for instance, in the context of stress contagion [95] and suicide prevention [96]. Consistent with the detected two-factor structure of the EES, Coll et al [18] proposed that emotional empathy might be the outcome of the two processes of Vicarious Experience and Intuitive Understanding of someone else’s emotions.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to a theoretical point of view, the Vicarious Experience and Intuitive Understanding components are also relevant from a clinical perspective in cases of pathology in which the exact deficits in empathy and intersubjectivity remain a topic of discussion (e.g., [88,8994]) and constitute possible targets of intervention, for instance, in the context of stress contagion [95] and suicide prevention [96]. Consistent with the detected two-factor structure of the EES, Coll et al [18] proposed that emotional empathy might be the outcome of the two processes of Vicarious Experience and Intuitive Understanding of someone else’s emotions.…”
Section: Discussionmentioning
confidence: 99%
“…The success of health care workers to establish a strong relationship with a sense of empathy with patients has been reported to have a great impact on the patients' recovery, perceived self-value, distress, satisfaction, and hope (29). Also, it has been shown that patients who feel compassionate empathy from their physicians and medical staff are more successful in overcoming acute symptoms more quickly and have strengthened immune systems (30). COVID-19 patients must endure not only severe physical conditions but also the stress of social and individual isolation due to the infectious nature of the virus, which disrupts their relationship with their family and friends and also healthcare workers.…”
Section: Discussionmentioning
confidence: 99%
“…The possibility that a patient's voice might become accessible in and through its refusal of conformity waxes when specific emotions are no longer seen as the property of either patient or physician but instead as the dynamic contents of a shared repertoire. (Weilenmann et al 2018). This commonality points to what Brennan, Teresa memorably terms the "transmission of affect," rooted in affect's deeply participatory nature, the sense in which feelings are by definition shared, arising situationally to become the common currency of those who feel them (2004,3).…”
Section: What Emotions Arise When Expectations and Ideals Are Violated?mentioning
confidence: 99%